2011
DOI: 10.1152/ajpendo.00175.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglucagonemia precedes a decline in insulin secretion and causes hyperglycemia in chronically glucose-infused rats

Abstract: GI, Kibbey RG. Hyperglucagonemia precedes a decline in insulin secretion and causes hyperglycemia in chronically glucose-infused rats. Am J Physiol Endocrinol Metab 301: E1174 -E1183, 2011. First published August 23, 2011; doi:10.1152/ajpendo.00175.2011.-Islet damage from glucose toxicity is implicated in the pathogenesis of type 2 diabetes, but the sequence of events leading to islet cell dysfunction and hyperglycemia remains unclear. To examine the early stages of islet pathology resulting from increased bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…In 1974, it was reported that hyperglycemia paradoxically stimulates glucagon secretion in dogs with chemically induced diabetes (10). More recently, plasma glucagon concentrations were reported to rise, with a tripling of hepatic glucose production, in normal rats continuously infused with glucose at a constant rate (11). Thus, there is evidence that in the absence of adequate insulin, elevated glucose might stimulate glucagon production, which in turn aggravates hyperglycemia.…”
mentioning
confidence: 99%
“…In 1974, it was reported that hyperglycemia paradoxically stimulates glucagon secretion in dogs with chemically induced diabetes (10). More recently, plasma glucagon concentrations were reported to rise, with a tripling of hepatic glucose production, in normal rats continuously infused with glucose at a constant rate (11). Thus, there is evidence that in the absence of adequate insulin, elevated glucose might stimulate glucagon production, which in turn aggravates hyperglycemia.…”
mentioning
confidence: 99%
“…The elegant studies of Jamison et al (39) provide strong tangible support for this theory. As recently reviewed, the α-cell defect in that disorder consists of failure to suppress glucagon during influx of nutrients because of defective paracrine signaling from β-cells (38).…”
Section: Discussionmentioning
confidence: 91%
“…At the end of the studies, rats were anesthetized with intravenous pentobarbital, and tissues were freeze-clamped and stored at Ϫ80°C for later analysis of hepatic glycogen, triglycerides, and mRNA (15,21,22). To minimize disturbance, rats were swivel-harnessed for the fasting studies and had free access to the cage (15). Glucose turnover rates were determined by primed continuous infusion of 99% D- [6,6-D 2 ]glucose (21,22).…”
Section: Methodsmentioning
confidence: 99%
“…PEPCK-M lacks the strong transcriptional regulation that is characteristic of PEPCK-C (9). An exception is in the chronically glucose-infused rat where augmented PEPCK-M expression accommodates the pathogenic increase in gluconeogenesis (15). The importance of PEPCK-C to human diabetes has recently come under additional scrutiny because PEPCK-C mRNA, protein, and activity from liver biopsy of humans with type 2 diabetes do not correlate with EGP (16).…”
mentioning
confidence: 99%